2020
DOI: 10.1111/1460-6984.12531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reasoning and hypothesis generation in expert clinical swallowing examinations

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Accurate severity rating requires access to a range of patient information that cannot be captured by either a single swallow-respiratory assessment nor an isolated instrumental assessment. Holistic dysphagia management requires multifaceted patient/clinical information and high-level clinical reasoning (Doeltgen, McAllister, Murray, Ward, & Pretz, 2018;McAllister et al, 2020).…”
Section: Cervical Auscultation: Impact Of Outcome Measures and Decision Makingmentioning
confidence: 99%
See 3 more Smart Citations
“…Accurate severity rating requires access to a range of patient information that cannot be captured by either a single swallow-respiratory assessment nor an isolated instrumental assessment. Holistic dysphagia management requires multifaceted patient/clinical information and high-level clinical reasoning (Doeltgen, McAllister, Murray, Ward, & Pretz, 2018;McAllister et al, 2020).…”
Section: Cervical Auscultation: Impact Of Outcome Measures and Decision Makingmentioning
confidence: 99%
“…The CSE has been criticised for its lack of diagnostic ability, particularly in identifying aspiration. Yet, it has also been argued that the CSE is an essential part of holistic dysphagia management for acute-care with rapidly changing patient status, short lengths of stay; and non-acute care where patient behaviour, co-morbidities, fatigue, and fluctuations in physical, respiratory and cognitive abilities, are important considerations for safe eating (American Speech-Language-Hearing Association (ASHA), 2020; McAllister et al, 2020) This is particularly relevant when considering oral intake over an entire meal and mealtime behaviours for people with dementia, COPD exacerbations, cerebral palsy, traumatic brain injury, and others (ASHA, 2020;Howle, Baguley, & Brown, 2014;Lewis, Walterfang, Velakoulis, & Vogel, 2018). The CSE þ CA allows for functional assessment, ongoing follow-up and regular patient contact, facilitating person-centred care.…”
Section: Holistic Dysphagia Assessment: Cervical Auscultation As An Adjunct To the Clinical Swallow Exammentioning
confidence: 99%
See 2 more Smart Citations
“…The value of clinical reasoning is well established within dysphagia practice. Doeltgen et al ( 2019 ), and many others (Jones, Cartwright, Whitworth, & Cocks, 2018 ; Mathers-Schmidt & Kurlinski, 2003 ; McAllister et al, 2020 ; Pettigrew & O’Toole, 2007 ; Rumbach, Coombes, & Doeltgen, 2018 ), have shown that sound clinical reasoning is vital within dysphagia assessment and management to prevent poor patient outcomes. However, almost all this research has emerged from higher income contexts which cannot always be generalised to LMICs.…”
Section: Introductionmentioning
confidence: 99%